The Histological Alteration of Proximal Part of Aorta Exposed to (MSG) and Protective Effect of an a Lipoic Acid (ALA) in Male Rabbits (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background. Monosodium Glutamate is one of the most world’s most widely used food additives. Its toxiceffect have been shown in numerous animal studies, in which study MSG effects on cardiovascular system,therefore, This study was aimed to investigate the effect of alpha lipoic acid(ALA) on the damage in thelarge blood vessels induce by Mono sodium glutamate. Thirty two male rabbits was divided equally andrandomly into four groups as following. Control group in which rabbits where fed with normal diet withoutsupplementation, second group was gived MSG orally (8mg/kg.BW), While animals of third group weregiven ALA orally (60mg/kg.BW) while animal in fourth group were given orally (MSG 8mg/kg.bw andALA 60mg/kg.bw), all treatment are extended to 8 weeks. The outcomes of research revealed a significantincreased (p<0.05) in aortic medial layer thickness in animals administration of MSG in a comparesionwith control and groups treated and distortion structure of laminar fibers, endothelial cells lost normalsquamous. In addition, there is a significant decreased (p<0.05) in medial tunica thicken in animals usedALA combination with MSG, so we noted return the disarranged of architecture tissue near.